Local Government Innovation in Agriculture Development: A Case Study of Bantaeng Regency, Indonesia - Badu Ahmad; Andi Ahmad Yani; Rakhmat Rakhmat (Iapa Proceedings Conference, 2020)
The study of local government innovation in arts development aims to comprehensively reveal and explain the forms of innovation applied by the Bantaeng Regency Government in accelerating agricultural development in the fields of horticulture, plantations and animal husbandry. This study uses a descriptive qualitative approach with phenomenological research to describe and explain the contribution of agricultural innovation in improving farmer welfare and food security in Bantaeng Regency. To obtain valid information, informants are determined by purposive sampling.To government officials and farmer groups involved in the fields of horticulture, plantations and animal husbandry with the hope that the interviewed informants and the implementation of the FGD understand the substance of the problem. The results of the study show that there are two main reasons for local governments to innovate in the agricultural sector, including the increasing population of 187,626 people. and agricultural land is increasingly limited, covering an area of 27,074.45 hectares. There are thirteen innovations implemented in accelerating agricultural development in Bantaeng Regency. these agricultural innovations include: regency producing seed technology based movement cropping systems legowo-21, agro-area development, enterprises owned by village , agricultural products processing, development engineering insemination cattle, utilizing waste livestock for biogas in rural areas, utilizing food waste for livestock feeding, breeding Bantaeng taro, cultivating special durian without aroma and season, cattle business insurance, rice planting insurance, guaranteed availability of fertilizers and seeds.